High‐Resolution Multi‐Isotope Imaging Mass Spectrometry (MIMS) Imaging Applications in Stem Cell Biology. Issue 11 (17th November 2021) - McMahon, G.; Lechene, C.P.
Abstract: Multi‐isotope imaging mass spectrometry (MIMS) allows the measurement of turnover of molecules within intracellular compartments with a spatial resolution down to 30 nm. We use molecules enriched in stable isotopes administered to animals by diet or injection, or to cells through the culture medium. The stable isotopes used are, in general, 15 N, 13 C, 18 O, and 2 H. For stem cell studies, we essentially use 15 N‐thymidine, 13 C‐thymidine, and 81 Br from BrdU. This protocol describes the practical use of MIMS with specific reference to applications in stem cell research. This includes choice and administration of stable isotope label(s), sample preparation, best practice for high‐resolution imaging, secondary ion mass spectrometry using the Cameca NanoSIMS 50L, and methods for robust statistical analysis of label incorporation in regions of interest (ROI). © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Stable isotope labeling of DNA in cultured cells Basic Protocol 2 : Stable isotope labeling of DNA in animals Basic Protocol 3 : Preparation of Si chips, the general sample support for NanoSIMS analysis Basic Protocol 4 : Stable isotope analysis of DNA replication in single nuclei in a population of cells with NanoSIMS Basic Protocol 5 : Data reduction and processing